2020
DOI: 10.1007/s40003-020-00498-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Puddling Techniques on Puddling Quality of Silty Loam Soil

Abstract: Paddy is the major cereal crop grown under standing water condition in agricultural fields. Puddling operation is carried out to facilitate standing water condition by creating an impervious layer in the subsoil surface. Puddling is a land preparation practice that will decide the water requirement in field throughout the cropping period. Different puddling techniques like puddling with cage wheel, rotavator, cage wheel ? rotavator and power tiller operated rotary tool were evaluated in a silty loam soil with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Normally, weed control requires a lot of labour (Lhungdim et al 2019); hence the use of chemicals (herbicides) for weed control before planting worth to be trying (Gangireddy and Subramanyam 2020). The soil tillage activities for rice cultivation in paddy fields do not absolutely require tillage because the availability of water in paddy fields can actually help the puddling process (Prasanthkumar et al 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, weed control requires a lot of labour (Lhungdim et al 2019); hence the use of chemicals (herbicides) for weed control before planting worth to be trying (Gangireddy and Subramanyam 2020). The soil tillage activities for rice cultivation in paddy fields do not absolutely require tillage because the availability of water in paddy fields can actually help the puddling process (Prasanthkumar et al 2021).…”
mentioning
confidence: 99%
“…For preparing the soil to plant rice, the most important thing is that the paddy field must be clean of weeds. Some studies have reported that weed control using herbicides is quite effective and can save labour (Prasanthkumar et al 2021). The application of conservation tillage (no-tillage) saves soil and water and can save energy, costs, and time (Neugschwandtner et al 2014(Neugschwandtner et al , Çay 2018.…”
mentioning
confidence: 99%